Creating a trauma- informed culture: Practicality in schools - Shoko, Ratidzai (Universitas PGRI Madiun, 2024)
Traumatic life experiences have an impact on learning, behaviour, and relationships in schools. A trauma-informed culture instilled in schools could significantly reduce the effects of traumatic experiences on learners, however, creating this may present challenges in schools. This article used secondary data from scholarly articles to investigate the practicality of creating a trauma- informed culture in schools. It was found that fostering a trauma-informed culture in educational settings is challenging since there are not enough qualified teachers or resources, and some activities cannot be done during school hours. It is recommended that proper training be provided to the educators and enough resources be availed to enable proper creation of a trauma- informed culture in schools.